Studi Kasus Asuhan Gizi pada Pasien Post Operasi Mioma Uteri dengan Anemia dan Diabetes Mellitus - Yurindraswari , Evana; Pitaloka, Diana Mareta Ida Fitri Ayu (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2025)
Uterine myoma is one of the benign tumors that is often found in reproductive-age women and often requires surgical intervention. Postoperative conditions become more complex when accompanied by comorbidities, iron deficiency anemia and type 2 diabetes mellitus (T2DM) which can slow recovery progression. The aim of this study is to describe the nutritional care process of patients after uterine myoma surgery with anemia and T2DM, including assessment, diagnosis, intervention, as well as monitoring and evaluation. The study design used an instrumental single-case study on a 43-year-old female patient who was hospitalized in the operating room for 4 days. Data were collected through anthropometric measurements (Mid Upper Arm Circumference/ MUAC and ulna length), biochemical analysis of medical records, daily 24-hour recall, Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), and pre/post test. The results showed that patients experienced malnutrition based on MUAC (18.3 cm), severe anemia (Hb 7.9 g/dL), and hyperglycemia (blood glucose 284 mg/dL). Intake of energy, protein, fat, carbohydrates, fiber, and iron was classified as a severe deficit before the intervention. After feeding a high-protein DM diet with small and frequent portions, the average intake increased to 79.9% energy and 108.5% protein from the daily requirement. Nutrition education improves patient knowledge scores even though the changes are not significant. In conclusion, structured nutritional interventions are able to improve the nutritional adequacy of patients even though the improvement in nutritional status has not been significant in a short time.